P53 Incidence of idiopathic pulmonary fibrosis in people with type 2 diabetes: the fremantle diabetes study. (12th November 2019) - Davis, WA; Navaratnam, V; Hubbard, RB; Davis, TME
Abstract : Background: Most studies that have examined the relationship between diabetes and idiopathic pulmonary fibrosis (IPF) have utilized administrative databases and/or have had limited/incomplete data. The aim of this study was to determine the incidence of IPF in a well-characterized community-based cohort of people with type 2 diabetes compared with a matched cohort without diabetes. Methods: The Fremantle Diabetes Study (FDS) Phase I type 2 diabetes cohort and four randomly-selected, age-, sex- and postcode-matched people without diabetes per FDS participant were followed through the Western Australian Data Linkage System for hospitalisation for/with and death from/with IPF from study entry (1993–6) until end-2017. Incidence rates (IRs) and IR ratios (IRRs) were calculated. Cox regression models adjusting for age, sex and co-morbidities were generated to ascertain the cause-specific (cs) hazard ratios (HR) for incident IPF by type 2 diabetes status. Results: Mean age of the pooled cohorts was 64 years (SD 11.2) and 49% were male. Eight (3 with type 2 diabetes) participants who had prevalent IPF were excluded. Mean follow-up was 16.6 (SD 7.6) years, during which 17 (1.3%) of the type 2 diabetes cohort and 57 (1.1%) of the no diabetes cohort developed incident IPF. This equates to IRs of 90.6 (95% CI 52.8–145.1) and 64.7 (95% CI 49.0–83.8) per 100, 000 person-years respectively. The crude IRR for incident IPF in people with type 2 diabetes compared to those without diabetes was 1.40 (95% CI 0.76–2.44; p=0.22). The cumulative incidence of IPF for people with type 2 diabetes versus no diabetes with age as the time line was higher, but statistically non-significant (p=0.13; see Figure 1).After adjusting for confounders, type 2 diabetes was associated with a csHR for IPF of 1.43 (95% CI 0.83–2.47). Conclusion: In a cohort of community-based individuals with type 2 diabetes, few had prevalent IPF or developed IPF during follow-up, due partly to the competing risk of death from other causes. Within the limitations of an uncommon outcome in a restricted sample, with more intensive cardiovascular and diabetes management, it is likely that greater rates of IPF will emerge in future.